Are Public or Private Providers of Employment Services More Effective? Evidence from a Randomized Experiment - Kai Rehwald; Michael Rosholm; Michael Svarer (Institute for the Study of Labor (IZA), 2015)
This paper compares the effectiveness of public and private providers of employment services. Reporting from a randomized field experiment conducted in Denmark we assess empirically the case for contracting out employment services for a well-defined group of highly educated job-seekers (unemployed holding a university degree). Our findings suggest, first, that private providers deliver more intense, employment-oriented, and earlier services. Second, public and private provision of employment services are equally effective regarding subsequent labour market outcomes. And third, the two competing service delivery systems appear to be equally costly from a public spending perspective.
Keywords: J64; J68; H41; H43; H44; L33; 330; active labour market policies; job-search assistance; contracting out; private provision of employment services; treatment effect evaluation; randomized trial; cost-analysis